PIM1 regulates glycolysis and promotes tumor progression in hepatocellular carcinoma - Leung, Carmen Oi-ning; Wong, Carmen Chak-lui; Fan, Dorothy Ngo-yin; Kai, Alan Ka-lun; Tung, Edmund Kwok-kwan; Xu, Iris Ming-jing; Ng, Irene Oi-lin; Lo, Regina Cheuk-lam (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is characteristically one of the most rapidly proliferating tumors which outgrows functional blood supply and results in regional oxygen deprivation. Overexpression of PIM1, a serine/threonine kinase, has been identified recently in human cancers. Knowledge on PIM1 in HCC is however, scarce. By immunohistochemical analysis on 56 human primary HCC samples, we observed overexpression of PIM1 in 39% of the cases. In two independent cohorts of paired primary and extra-hepatic metastatic HCC tissues, PIM1 expression was higher (p=0.002) in the extra-hepatic metastatic HCC tissues as compared with the corresponding primary HCCs. PIM1 was markedly up-regulated in multiple HCC cell lines in hypoxic condition (1% O2) versus normoxia (20% O2). Silencing of PIM1 suppressed HCC cell invasion in vitro as compared to non-target control, and decreased HCC cell proliferation in vitro and tumor growth and metastatic potential in vivo. Knockdown of PIM1 significantly reduced glucose uptake by HCC cells and was associated with decreased levels of p-AKT and key molecules in the glycolytic pathway. Taken together, PIM1 is up-regulated by hypoxia in HCC and promotes tumor growth and metastasis through facilitating cancer cell glycolysis. Targeting PIM1 may have potential role in the management of HCC.